2015
DOI: 10.1007/s00284-015-0916-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Bohai Bay Solar Saltworks, China

Abstract: The microbiota in solar salterns plays an important role in salt production quantitatively and qualitatively. Bohai Bay coast is the major sea salt producing area in China. However, few ecological characterization studies of the Bohai Bay salt ponds, particularly of their microbial diversity, have been conducted. This study investigated the structure and diversity of the bacterial community in Hangu saltworks in response to environmental factors. The brine water was sampled from five selected saltponds within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Like several other salterns and hypersaline environments, Siridao salterns support diverse communities of phylotypes belonging to Bacteroidetes and Gammaproteobacteria (Sørensen et al, 2005;Baati et al, 2011;Zhang et al, 2016). The occurence of Alphaproteobacteria, Betaproteobacteria and Firmicutes decreased with increasing salinity which was consistent with the results obtained by Oueriaghli et al (2018).…”
Section: Major Shifts In Bacterial Diversity Between Salt Production supporting
confidence: 85%
See 1 more Smart Citation
“…Like several other salterns and hypersaline environments, Siridao salterns support diverse communities of phylotypes belonging to Bacteroidetes and Gammaproteobacteria (Sørensen et al, 2005;Baati et al, 2011;Zhang et al, 2016). The occurence of Alphaproteobacteria, Betaproteobacteria and Firmicutes decreased with increasing salinity which was consistent with the results obtained by Oueriaghli et al (2018).…”
Section: Major Shifts In Bacterial Diversity Between Salt Production supporting
confidence: 85%
“…In the intermediate salinity samples (13–18%), bacterial phylotypes affiliated to phyla Proteobacteria , Bacteroidetes , Actinobacteria , and Verrumicrobia were usually encountered while the archaeal members belonged to genera Halorubrum , Haloarcula , and Haloquadratum (phylum Euryarchaeota ). High salinity samples (>25%) were dominated by halophilic archaea belonging to genera such as Haloquadratum and Halorubrum along with a minor contribution from bacterial phylotypes belonging to Bacteroidetes (genus Salinibacter ) ( Mouné et al, 2003 ; Pašić et al, 2005 ; Sørensen et al, 2005 ; Park et al, 2006 ; Wang et al, 2007 ; Baati et al, 2008 , 2010 ; Tsiamis et al, 2008 ; Manikandan et al, 2009 ; Oren et al, 2009 ; Oh et al, 2010 ; López-López et al, 2010 ; Zafrilla et al, 2010 ; Tkavc et al, 2011 ; Trigui et al, 2011 ; Boujelben et al, 2012 ; Dillon et al, 2013 ; Fernandez et al, 2014a , b ; Mani et al, 2015 ; Çinar and Mutlu, 2016 ; Di Meglio et al, 2016 ; Zhang et al, 2016 ; Kalwasińska et al, 2018 ; Leoni et al, 2020 ). In general, archaeal composition from the total prokaryotic community was observed to be between 27–46% at intermediate salinities (13–19%) and 80–90% at high salinities (>25%) ( Ghai et al, 2011 ; Fernandez et al, 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…where N is the number of bands contained in the sample (one DGGE lane) and D is the denaturing percentage range in which these bands are found. It is considered low richness (low diversity) when Rr < 10, mean when 10 < Rr < 30, and high when Rr > 30 [62]. This analysis is appropriate when the BTF has been inoculated with a known bacterial community or strain, so that each of the DGGE lanes and their Rr will indicate if the community or strain changes according to operational changes in the BTF.…”
Section: Dgge Protocolmentioning
confidence: 99%
“…A representative and valuable fungal Chinese herb is Cordyceps ( Ophiocordyceps sinensis ). In the study of O. sinensis , Zhang et al [55] used 2-DE and MALDI-TOF/TOF–MS to compare proteins of O. sinensis samples that five were collected from different habitats (three from China, two respectively from Nepal and Bhutan) and other four were different fungal specimens with similar shape; They found that distribution of O. sinensis protein spots among the five regions has no striking differences, and two specific proteins OCS_04585 and b-lactamase domain-containing protein were identified, while the comparison results between four fungal specimens showed that there was only one common protein (protein-eliciting plant response-like protein) existed. A more extensive research about habitats was carried out by Li [56] to find differentially expressed protein of O. sinensis .…”
Section: Identifications Of Traditional Chinese Medicines By Differenmentioning
confidence: 99%